Customized Woven Carbon Fiber Electrodes for Bioelectrochemical Systems—A Study of Structural Parameters - Pötschke, Liesa; Huber, Philipp; Stegschuster, Georg; Schriever, Sascha; Kroppen, Norman; Schmatz, Joyce; Gries, Thomas; Blank, Lars M.; Farber, Peter; Rosenbaum, Miriam A. (Frontiers in Chemical Engineering, 2022)
Commercial carbon fiber (CF) fabrics are popular electrode materials for bioelectrochemical systems (BES), but are usually not optimized for the specific application. This study investigates BES relevant material characteristics on fabric level, such as weave types and weave parameters. The two contrasting weave types plain and leno weave were characterized with respect to their envisaged application types: 1) BES with mainly advective flow regimes and 2) stirred systems, which could benefit from fluid flow through a fabric electrode. Experiments with batch and continuously fed pure cultures of Geobacter sulfurreducens PCA and Shewanella oneidensis MR-1 reveal that µm scale electrode topologies are of limited use for the thick biofilms of G. sulfurreducens, but can boost S. oneidensis’ current generation especially in batch and fed-batch reactors. For advective flow regimes, deeper layers of biofilm inside microporous electrodes are often mass transport limited, even with thin biofilms of S. oneidensis. Therefore, low porosity plain weave electrodes for advective flow operation as in wastewater treating BES should be thin and flat. A trade-off between maximized current density and electrode material utilization exists, which is optimized exemplarily for an advective flow operation. For stirred BES of biotechnological applications, a flow-through of electrolyte is desired. For this, leno weave fabrics with pores at cm scale are produced from 100 % CF for the first time. In a preliminary evaluation, they outperform plain weave fabrics. Mass transfer investigations in stirred BES demonstrate that the large pores enable efficient electrode utilization at lower power input in terms of stirring speed.